Optimalisasi Potensi Ekonomi Syariah dalam Populasi Muslim Global untuk Mendukung Pencapaian SDGS: Studi Strategis tentang Zakat, Wakaf, dan Industri Halal - Jauharudin, Fahmi; Khusnudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The global Muslim population, exceeding 1.9 billion, holds significant potential to support the achievement of the Sustainable Development Goals (SDGs). Through Islamic economic instruments such as zakat, waqf, and the development of the halal industry, substantial contributions can be made to poverty alleviation, improving education quality, and promoting sustainable consumption and production. This study identifies major challenges, including the lack of regulatory harmonization, low Islamic financial literacy, and limited international cooperation. On the other hand, substantial opportunities arise from technological innovation, global collaboration, and growing international interest in halal products. Strategies such as enhancing Islamic financial literacy, leveraging digital technology, and harmonizing policies across countries can optimize Islamic economics to support global sustainable development.